Identity of communicants in certain type of political interview in the media - Svobodová, Jindřiška (Bohemica Olomucensia, 2013)
The author analyses the material and states that course and final character of dialogues is although influenced by the speaker's initial aims, but in the same time is visible that not all of the dialogues are constructed using simultaneous principles of cooperation. Well-marked is speaker's tendency to enforce and to maximalize the own profit from the dialogue, and to make a loss of image on the side of partner in the communication.